Genome-wide Identification and Expression Analysis of Calcium-dependent Protein Kinase and Its Closely Related Kinase Genes in Capsicum annuum - cai, hanyang; cheng, junbin; yan, yan; xiao, zhuoli; li, jiazhi; mou, shaoliang; qiu, ailian; lai, yan; guan, deyi; He, Shuilin (Frontiers in Plant Science, 2015)
As Ca2+ sensors and effectors, calcium-dependent protein kinases (CDPKs) play important roles in regulating the downstream components of calcium signaling, which are ubiquitously involved in plant growth, development, and response to environmental cues. However, no CDPKs have been characterized in Capsicum annuum thus far. Herein, a comprehensive analysis of genes encoding pepper CDPKs and CDPK-related protein kinases (CRKs) was performed, and 31 CDPK genes and five closely related kinase genes were identified, which were phylogenetically divided into four distinct subfamilies and unevenly distributed across nine chromosomes. Conserved sequence and exon-intron structures were found to be shared by pepper CDPKs within the same subfamily, and the expansion of the CaCPK family in pepper was found to be due to segmental duplication events. Five CDPKs in the Capsicum annuum variety CM334 were found to be mutated in the Chiltepin variety, and one CDPK present in CM334 was lost in Chiltepin. The majority of CDPK and CRK genes were expressed in different pepper tissues and developmental stages, and 10, 12, and eight CDPK genes were transcriptionally modified by salt, heat, and Ralstonia solanacearum stresses, respectively. Furthermore, these genes were found to respond specifically to one stress as well as respond synergistically to two stresses or three stresses, suggesting that these CDPK genes might be involved in the specific or synergistic response of pepper to salt, heat, and R. solanacearum. Our results lay the foundation for future functional characterization of pepper CDPK and its closely related gene families.